Historia Genealogica da Casa Real Portugueza - D. Antonio Caetano De Sousa (Regia Officina Sylviana, 1748)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; History

Histoire General des Voyages, Nao Consta, Chez Perre de Hondt - Perre, Chez (1748)
Reference Link: https://www.abebooks.fr/HISTOIRE-GENERALE-VOYAGES-NOUVELLE-COLLECTION-RELATIONS/19268585964/bd
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Histoire General des Voyages, Nao Consta, Chez Perre de Hondt - Perre, Chez (1748)
Reference Link: https://www.abebooks.fr/HISTOIRE-GENERALE-VOYAGES-NOUVELLE-COLLECTION-RELATIONS/19268585964/bd
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage